When pay increases are not enough: The economic value of wage Delegation in the field - Sabrina Jeworrek; Vanessa Mertins (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2014)
By conducting a natural field experiment, we test whether a managerial policy of allowing employees to self-determine their wages is as successful as recently suggested by laboratory evidence. We find that this policy indeed enhances performance. However, our data is clearly at odds with the conjecture of Pareto improvements, since labor costs grow even faster. Admittedly, the performance change is remarkable given that a considerable pay increase has no effect at all. Surprisingly, the data suggests that explicitly denying parts of the workforce this choice boosts performance, too. Additional experimental and survey data provides important insights into employees' underlying motivations.
Keywords: C91; C93; J33; M52; M54; 330; Field experiment; Delegation; Reciprocity; Responsibility alleviation; Compensation; Worker empowerment; Workplace democracy